Coagulant Activity Deposited on the Kiil Haemodialysis Membranes - Lurie, A; Denson, K. W. E (Thrombosis and Haemostasis, 1970)
A deposit present on the dialysing membranes of Kiil renal dialysis machines after extracorporeal haemodialysis has been found to have coagulant activity with features similar to phospholipid and to the thromboplastic activity of platelets. The deposition of the coagulant material occurred in spite of anti-coagulation with heparin. It is postulated that this coagulant material may render the extracorporeal blood hypercoagulable, and that this may be of significance in the pathogenesis of thrombosis in the shunt vasculature.